Agricultural commercialization and diversification in Bhutan - Minten, Bart; Pradhan, Kailash (International Food Policy Research Institute, 2010)
Bhutan has shown good economic growth (9% annually) in the 9th Five-Year Plan (FYP) (2002-2007) and is further continuing on this growth path in the 10th FYP. As domestic incomes rise because of this growth, Bhutanese consumers are expected to shift their consumption patterns from staple grains to fruits, vegetables, dairy, eggs, and meat, leading to an increase in demand for these high-value agricultural products. Likewise, as Bhutan becomes integrated into the regional and global economy, farmers will diversify into high-value agricultural products that are in demand in urban areas of its South-Asian neighbors and in highincome countries. This is particularly true since, within South-Asia, Bhutan has a comparative advantage in temperate and sub-tropical commodities.